A CLINICAL CASE OF CROHN’S DISEASE - Bohun, N. Yu.; Kushnir, I. E.; Chernyak, A. M.; Belal, S. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 2018)
The article demonstrates a clinical case of Crohn’s disease. The clinical manifestation of the disease, a diagnostic approach based on laboratory and instrumental methods with discussion of obtained results, and the up-to-date methods of investigation based on the literature data are shown. The significance of lifestyle modification, optimal drug treatment and regular check-ups for improvement of prognosis is emphasized. TreatmentGeneral approach includes smoking cessation; lactose-free diet in case of secondary lactose intolerance which is present in approximately one third of cases; in the case of malabsorption syndrome appropriate replacement of vitamins, calories, protein, zinc, calcium and other nutrients is considered. Treatment bile acid diarrhea includes administration of ion-exchange resins to bind bile acids (e.g., cholestyramine).During acute episodes recommendations to avoid dietary fibers should be given and parenteral nutrition can be prescribed.Our patient received drug therapy: reosorbilact solution 200,0ml during four. The goal of treatment of CD is thus to slow the progression of the disease, avoid recurrence of inflammatory episodes and prevent complications which are extremely common in the absence of optimal treatment. Life expectancy is normal and quality of life may be satisfactory with aggressive evidence-based treatment. Majority of patients (approximately 70%) requires surgical operations due to complications within 15years of their onset.